Pengaruh Problematic Internet Use Terhadap Subjective Well-Being Pada Mahasiswa Universitas Islam Bandung - Nisa Nurafifah; Muhammad Ilmi Hatta (Bandung Conference Series: Psychology Science, 2023)
Abstract. Students who experience anxiety, stress, and experience problematic internet use can have low subjective well-being (Hui et al., 2011; Chen, 2011). Students are prone to experiencing problematic internet use, because the University itself provides wifi that can be accessed anywhere, besides that students also have a lot of free time because there is no definite schedule (Frangos et al., 2011). According to Caplan (2010) problematic internet use is the existence of excessive internet use characterized by certain characteristics of behavior and cognition, which causes a negative impact both in learning and social. The purpose of this study was to determine the effect of problematic internet use on subjective well-being in students of the Islamic University of Bandung. The research method used in this study is quantitative with a causality research design. The measuring instrument for problematic internet use is the Generalized Problematic internet use Scale 2 (GPIUS2), while for subjective well-being using the satisfaction with life scale (SWLS) and the Postive and Negative Affect Scale (SPANE). The sample taken was 390 students. And the results showed that problematic internet use has a negative effect on subjective well-being. The partial determination coefficient test results show that problematic internet use affects SWLS by 11.1%, while SPANE by 44.8%. This means that problematic internet use has a negative and significant influence on subjective well-being with affective aspects, namely through the Postive and Negative Affect Scale (SPANE) which has the greatest influence on problematic internet use in Bandung Islamic University students. Abstrak. Mahasiswa yang mengalami kecemasan, stress, serta mengalami problematic internet use dapat memiliki subjective well-being yang rendah (Hui et al., 2011; Chen, 2011). Mahasiswa rawan mengalami problematic internet use, karena di Universitas sendiri menyediakan wifi yang dapat diakses dimana saja, selain itu mahasiswa juga banyak memiliki waktu luang karena tidak ada jadwal yang pasti (Frangos et al., 2011). Menurut Caplan (2010) problematic internet use adalah adanya penggunaan internet yang berlebihan yang ditandai dengan ciri tertentu dari perilaku serta kognisi, yang menyebabkan adanya dampak negatif baik dalam pembelajaran maupun sosial. Tujuan dari penelitian ini adalah untuk mengatahui pengaruh problematic internet use terhadap subjective well-being pada mahasiswa Universitas Islam Bandung. Metode penelitian yang digunakan dalam penelitian ini adalah kuantitatif dengan desain penelitian kausalitas. Alat ukur problematic internet use adalah Generalized Problematic internet use Scale 2 (GPIUS2), sedangkan untuk subjective well-being menggunakan alat ukur satisfaction with life scale (SWLS) dan Scale Postive and Negative Affect (SPANE). Sampel yang yang diambil sebanyak 390 mahasiswa. Dan didapatkan hasil bahwa problematic internet use berpengaruh negatif terhadap subjective well-being. Hasil uji koefisien determinasi parsial menunjukan bahwa problematic internet use berpengaruh terhadap SWLS sebesar 11,1%, sedangkan SPANE sebesar 44,8%. Artinya problematic internet use memiliki pengaruh negatif dan signifikan terhadap subjective well-being dengan aspek afektif yakni melaui Scale Postive and Negative Affect (SPANE) yang memiliki pengaruh paling besar problematic internet use pada mahasiswa Universitas Islam Bandung.